C02 Molecular Analysis Of The Zq175 Knock-in Mouse Model. (17th September 2014) - Ali, NS; Landles, C; Salsbury, G; Osborne, GF; Benjamin, AC; Lazell, H; Goodwin, D; Smith, DL; Franklin, SA; Bates, GP
Abstract : Background: The zQ175 knock-in line was generated by replacing mouse endogenous Htt exon 1 with a mutant version of human HTT exon 1 followed by the expansion of the CAG repeat. This line is now being used extensively throughout the HD research community. Method: We have performed a molecular analysis to study changes in mutant HTT and the appearance of transcriptional dysregulation. We used immunoprecipitation and western blotting to visualise HTT fragments and found that the level of the exon 1 HTT fragment decreased from two months of age. Results: Seprion ELISA has indicated that there is a statistically significant level of HTT aggregation in striatum, cortex, hippocampus, cerebellum and the brain stem from 8 months of age, and the age at which these aggregates can first be detected is under investigation. We determined the expression levels of genes known to be dysregulated in HD brains in the striatum, cortex and cerebellum. The striatal genes: Pde10a and Penk1 were dysregulated by 6 months of age and Cnr1 and Darpp32 by 8 months in heterozygous zQ175 mice with good statistical power for detecting improvements. Conclusions: Therefore, we have identified molecular read-outs that can be used in the preclinical validation of therapeutic targets in heterozygous zQ175 mice.